2010
DOI: 10.1186/1475-2859-9-86
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess Control in Microscale: Scalable Fermentations in Disposable and User-Friendly Microfluidic Systems

Abstract: BackgroundThe efficiency of biotechnological production processes depends on selecting the best performing microbial strain and the optimal cultivation conditions. Thus, many experiments have to be conducted, which conflicts with the demand to speed up drug development processes. Consequently, there is a great need for high-throughput devices that allow rapid and reliable bioprocess development. This need is addressed, for example, by the fiber-optic online-monitoring system BioLector which utilizes the wells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…Analysis of the extracellular proteome revealed that the most abundant proteins have a periplasmic origin (64% of this extracellular proteome is composed of periplasmic and outer membrane proteins). This observation is in accordance with the results of Funke et al (2011)38 who found, respectively, 65% of periplasmic proteins and 56% of outer membrane proteins with the W3110 Escherichia coli strain. However, some major cytoplasmic proteins have been identified, such as chaperonin GroE , chaperone DnaK , and elongation factor Tu.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of the extracellular proteome revealed that the most abundant proteins have a periplasmic origin (64% of this extracellular proteome is composed of periplasmic and outer membrane proteins). This observation is in accordance with the results of Funke et al (2011)38 who found, respectively, 65% of periplasmic proteins and 56% of outer membrane proteins with the W3110 Escherichia coli strain. However, some major cytoplasmic proteins have been identified, such as chaperonin GroE , chaperone DnaK , and elongation factor Tu.…”
Section: Resultssupporting
confidence: 93%
“…Second, pH is not controlled in the mini‐bioreactors,33 potentially leading to the induction of some related regulation network linked with substrate starvation (i.e., general stress response pathway34–37). It must be noted that this technical issue could be corrected in the future by appropriate sensor‐actuator systems at the milliliter scale 23, 38. However, the media are buffered, so the maximum decrease in pH is 0.5 units (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In shaken systems, despite the significant advances in the monitoring of process variables, process control remains a limitation, making accurate determination of OUR in such devices challenging. In microtiter plates, this has been circumvented by applying feeding strategies to control pH and provide fed‐batch capabilities . Recently, several automated miniaturized systems based on plate formats have been commercialized, which have the ability to monitor and control in individual wells the pH, DO and temperature (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3B). Previously, other authors have shown correspondence between DO profiles and biomass production [29][30][31][32][33], suggesting that bacterial growth may be followed without the need for sampling or for interfering with the system. However, there were some discrepancies in the observed trends in biomass and DO in the case of M. smegmatis (Fig.…”
Section: Assessing Growthmentioning
confidence: 94%